2016
DOI: 10.1109/joe.2016.2527938
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Surface Current Measurement Using Shipborne HF Radar: Model and Analysis

Abstract: The extension of onshore high-frequency surface wave radar (HFSWR) to shipborne HFSWR has the advantage of extended monitoring area and high application flexibility. However, additional modulation on the echo signal introduced by the forward movement and six-degree-of-freedom (6-DOF) ship motion may increase the surface current measurement error. Considering the radar array position on the ship, six-DOF ship motion, forward movement velocity, first-order Bragg scatter, and background noise, this paper models t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Compared with the conventional method based on a land-based receiving array, this method was stated to be more easily realized with less system cost. Similarly, methods for ocean surface current extraction and ocean clutter spectrum estimation for shipborne HFSWR were developed in [26][27][28].…”
Section: Radar Cross Section Models For An Antenna On a Floating Platmentioning
confidence: 99%
“…Compared with the conventional method based on a land-based receiving array, this method was stated to be more easily realized with less system cost. Similarly, methods for ocean surface current extraction and ocean clutter spectrum estimation for shipborne HFSWR were developed in [26][27][28].…”
Section: Radar Cross Section Models For An Antenna On a Floating Platmentioning
confidence: 99%
“…The orbital velocity of the long waves is modeled as the function of time t and slant range r and can be written as Xin et al [3]: As shown in Figure 4, the orbital velocity of the long waves is time-varying and space-varying, the wave profile is the linear superposition of sinusoidal waves, and the orbital velocity of the long waves possesses the periodicity shown in Figure 4 [3,33]. The orbital velocity of the long waves is modeled as the function of time t and slant range r and can be written as Xin et al [3]: (8) where N w is the number of harmonic waves, A i is the amplitude of the ith harmonic sinusoidal wave, ω i is the angular velocity of the ith sinusoidal wave and k i is the wavenumber of the ith wave.…”
Section: Doppler Shift Of the Orbital Motions Of The Long Wavesmentioning
confidence: 99%
“…The Bragg scattering theory specifies that the radar is primarily sensitive to radially-traveling waves that satisfy the Bragg resonant condition, and the phase velocity of the Bragg resonant waves is also stable. Therefore, the high-frequency (HF) ocean surface current radar can measure the sea surface current velocity utilizing the Bragg scattering theory of the sea surface [5][6][7][8] and can be applied to estimate the sea surface current velocity of large areas; for example, the shore-based HF ocean surface current radar of the University of Miami has been used to measure the 2-D offshore surface current vectors from …”
Section: Introductionmentioning
confidence: 99%
“…In the previous works, however, the hull itself is either stationary or moving at a low speed without considering a high-speed case and effects of six DOFs motion on radar Doppler spectra. In this section, the potential of remote sensing of ocean surface radial current with shipborne HFSWR is presented [24]. Moreover, a stream function method is introduced to obtain current vector field using an improved music signal classification (MUSIC) algorithm and unitary transformation technique [25].…”
Section: Remote Sensing Of Ocean Surface Current With Shipborne Hfswrmentioning
confidence: 99%